Efeito da microadição de oxigênio na estabilidade microestrutural da liga Ti-29Nb-13Ta-4,6Zr processada via deformação plástica severa e envelhecimento - Silva, Murillo Romero da (2021)
Gum Metal corresponds to a family of β-Ti alloys that are currently receiving great attention due to its outstanding properties such as low elastic modulus, superelasticity, and high tensile strength. These alloys show only β-stabilizing, non-toxic, and biocompatible alloying elements. For the production of Gum Metal, it is recommended the addition of oxygen that is not tightly defined in the literature, as well as an accentuated cold work, which is usually obtained by cold rolling or swaging. The present work proposed to produce Gum Metal Ti-29Nb-13Ta-4.6Zr-xO (wt.%) with three different oxygen contents (700, 2200, and 4600 ppm) by an alternative processing route composed of rotary forging and severe plastic deformation (SPD) by HPT. Also, the work proposes to investigate alloy behavior during aging. This thesis aimed to find a microstructural condition that provides high mechanical strength while maintaining the Gum Metal typical low elastic modulus. The processed alloy in this work had its microstructure, mechanical, thermal, and physical properties investigated. An increase in β-phase stability, to the detriment of αʺ, as well as in the mechanical properties was observed with the combined effect of oxygen addition, HPT processing, and aging. The increase in mechanical properties was attributed to the microstructural refinement, with a grain size up to 50 nm, and to the high dislocation density, both obtained after SPD, and to the formation of finely dispersed precipitates in the β-matrix after aging. Microhardness of approximately 400 HV was obtained for samples in two different combinations of processing and oxygen level. The elastic modulus did not change significantly for the different oxygen levels, obtaining values between 58 to 70 GPa. The typical properties of Gum Metal were achieved in the present thesis, which is related to the deformation mechanisms such as slip, twinning, transformation-induced martensite as well as reverse martensitic transformation.